Relationship between depression and subclinical left ventricular changes in the general population. Issue 18 (28th July 2012) - Kim, Yong-Hyun; Kim, Seong Hwan; Lim, Sang Yup; Cho, Goo-Yeong; Baik, In-Kyung; Lim, Hong-Euy; Na, Jin Oh; Han, Seong Woo; Ko, Young-Hoon; Shin, Chol
Abstract : Objective: Individuals with depression are at risk of heart failure. This study was designed to elucidate the relationship between depression and subclinical left ventricular (LV) changes in the general Korean population. Design: Cross-sectional cohort study. Setting: University hospital. Patients: A total of 2420 participants, aged 40–79 years, without known cardiovascular disease, were recruited from the Korean Genome Epidemiology Study. Methods: All individuals underwent conventional two-dimensional echocardiography and tissue Doppler imaging (TDI) to measure LV changes. In addition, subjects answered the Beck depression inventory I (BDI-I) questionnaire to assess depression levels. Participants were assigned to one of three groups based on the BDI-I score: no depression (0≤ BDI-I <10), mild depression (10≤ BDI-I <20), and moderate to severe depression (BDI-I ≥20). Results: LV diastolic function parameters, such as the transmitral A wave velocity and E/A ratio, TDI early diastolic velocity (Ea ), and E/Ea ratio, were progressively altered across the levels of depression (all p<0.01). After multivariate adjustment, subjects with moderate to severe depression showed a significantly higher LV mass index (p=0.019) and lower TDI Ea velocity (p=0.006) compared with those without depression. In linear regression models, the presence of depression (BDI-I ≥10) was independently associated with a lower TDI Ea velocity (p=0.004). Conclusions: Individuals with moderate to severe depression showed subclinical alterations in LV structure and function. These findings support the hypothesis that clinical depression may be an independent risk factor for the development of cardiovascular disease.